The Effectiveness of Using Nearpod Learning Media Seen from the Interest in Learning Mathematics of Class XI Students at MAN 2 Sinjai - Ramadhani, Astri; Syarifuddin, Syarifuddin; Fitriani, Fitriani; Safaruddin, Safaruddin; Danial, Danial (JTMT: Journal Tadris Matematika, 2025)
This research aims to determine the effectiveness of using nearpod learning media in terms of students' interest in learning mathematics. The population and samples of this study were grade XI students. The type of research used in this study is pre-experimental research with a One group Pretest-Post test design with a quantitative approach. This research was conducted at MAN 2 Sinjai. The sample of this study amounted to 23 people using purposive sampling technique. The data collection methods used were observation and questionnaire of interest in learning mathematics. The data analysis technique used was descriptive test, data normality test, homogeneity test, N Gain test and hypothesis testing using paired sample t-test. The results of this study showed that nearpod learning media proved effective in terms of students' interest in learning mathematics. It can be seen from the results of descriptive analysis obtained that < or 45.17 < 72.91, meaning that the average interest in learning mathematics after nearpod media treatment is greater than before nearpod media treatment. In addition, the results of the hypothesis test using the paired sample t-test obtained a sig value of 0.001. The significance value is smaller than 0.05 or 0.001 <0.05. Thus, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. From these results it can be concluded that the nearpod learning media is effective in terms of interest in learning mathematics of grade XI students at MAN 2 Sinjai.